2013 IEEE International Symposium on Phased Array Systems and Technology 2013
DOI: 10.1109/array.2013.6731840
|View full text |Cite
|
Sign up to set email alerts
|

A method for improved cross-pol isolation based on the use of auxilliary elements

Abstract: This paper describes a method to answer the following questions: can several of the elements of a phased array be employed as auxiliary (AUX) elements and how can the phase of each be adjusted so that the (1) cross-polarization (cross-pol) isolation is minimized to 40 dB, (2) the sidelobe levels of the main lobe are minimally impacted, and (3) the width and height of the main lobe are minimally impacted? This calibration work is being completed as one component of Lincoln Laboratory's effort within the multifu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…This solution to the calibration challenge is an important advantage of fully digital PARs. Further discussion on the use of this approach for the Horus system appears in Section V. Recent work has also shown that polarimetric performance enhancements can be achieved with a fully digital array using the so-called cross-polar canceller (XPC) technique [61], [62], [63]. This method assigns a small number of elements from the entire array in an attempt to mitigate cross-polar contamination by transmitting the opposite phase from the original signal.…”
Section: A Calibration -Polarimetric Requirements For Weather Observa...mentioning
confidence: 99%
“…This solution to the calibration challenge is an important advantage of fully digital PARs. Further discussion on the use of this approach for the Horus system appears in Section V. Recent work has also shown that polarimetric performance enhancements can be achieved with a fully digital array using the so-called cross-polar canceller (XPC) technique [61], [62], [63]. This method assigns a small number of elements from the entire array in an attempt to mitigate cross-polar contamination by transmitting the opposite phase from the original signal.…”
Section: A Calibration -Polarimetric Requirements For Weather Observa...mentioning
confidence: 99%